An Inertial Forward-backward Splitting Method for Monotone Inclusions - Van Dung, Nguyen; Thi Kim Hoa, Hoang (VNU Journal of Science: Mathematics - Physics; Vol 41 No 1DO - 10.25073/2588-1124/vnumap.4900, 2025)
In this work, we propose a splitting method for solving monotone inclusions in Hilbert spaces. Our method is a modification of the forward-backward algorithm by using the inertial effect. The weak convergence of the proposed algorithm is established under standard conditions.